Analisis Hasil Pengawasan Iklan Produk Pangan Olahan di Provinsi DKI Jakarta pada tahun 2021-2023 - Saifudin, Umar; Noviardani, Tenri (Eruditio : Indonesia Journal of Food and Drug Safety, 2024)
Food is a fundamental need in society, and advertising significantly influences the consumption of processed food products. Advertising introduces products for businesses and provides product-related information for consumers. However, some advertisements violate regulations. Supervising processed food advertisements is one of the Indonesian Food and Drug Authority's (FDA) roles. This study analyzes processed food advertisement supervision in DKI Jakarta from 2021 to 2023, focusing on media types, violation types, and food categories most frequently violating regulations. Secondary data from supervision reports collected by the Jakarta FDA Office during this period were analyzed descriptively. Results show that 1468 (77.7%) of the 1890 advertisements evaluated did not meet regulatory requirements. Most violations occurred in online media (1424 ads, 97%), followed by outdoor media (39 ads, 2.7%) and print media (5 ads, 0.3%). The most common violations included health claims not complying with provisions (1110 ads, 75.7%), misleading advertisements (175 ads, 11.9%), prohibited advertising in non-health media (160 ads, 10.9%), superlative statements (21 ads, 1.4%), and norm violations (1 ad, 0.1%). Violations based on food categories were highest in beverages (category 14) with 1149 ads (78.3%), milk products (category 1) with 66 ads (4.5%), and sugar products and sweeteners (category 11) with 49 ads (3.3%). These findings highlight the need for stricter oversight and public awareness of advertising regulations.